The Role of E-Learning During the Covid-19 Pandemic in West Bengal: Advantageous, Problems and Ameliorate on Higher Learners Students - Suman Basu (Researchparks Publishing, 2022)
E-learning is a medium through which we use an electronic device to acquire and learn skills.E-learning expands the store of knowledge anytime and anywhere outside our educational and educational institutions. During the Covid-19 Pandemic we used this is learning as the only key to sustain our education system. Therefore, there is no doubt that e-learning is further advancing our education system. But in the past situation and in the present situation, we can say that not everyone is getting equal opportunity in the education system or learning through e-learning. The teachers and the students have to face a lot of problems when we or any Youtubers use any mobile or electronics device. That's why I personally selected 36 participants to facilitate this type of research who are deeply involved in learning in a variety of ways. And by collecting a lot of information from those selected students, I have shown here what kind of problems teachers and students have in the course of learning that hinder their learning. Again, how to get rid of those problems. In addition, we have tried to give an important idea of the advantages and disadvantages of the current education system in India.